PENERAPAN PENDEKATAN SUPERVISI KOLABORATIF UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SD NEGERI 2 PLANDI WONOSARI KABUPATEN MALANG - Mistiani, Mistiani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The results of empirical studies conducted by the researchers on teachers at Plandi Wonosari State Elementary School 2 Malang showed that teacher professional competence was still low, especially in teacher competencies in developing learning materials that were taught creatively. Considering these conditions, one of the efforts that can be carried out by researchers to overcome the problem of the low professional competence of teachers in carrying out their professional duties, then applied the action in the form of a supervision approach that has never been done before, namely the collaborative supervision approach. Based on the results of the study, it can be seen that there is an increase in teacher professional competence from pre-cycle to Cycle I of 18.18 points. The average professional competence of teachers in the pre-cycle is 52.27 with less criteria and in Cycle I is 70.45 with sufficient criteria. Teacher professional competence also experienced an increase from Cycle I to Cycle II by 18.19 points. The average professional competence of teachers in Cycle II was 88.64 with good criteria